The origin of concepts - Carey, Susan (New York ; Oxford : Oxford University Press, 2009)
Carey characterizes the innate starting point for conceptual development, namely systems of core cognition. She also argues that the key to understanding cognitive development lies in recognizing conceptual discontinuities in which new representational systems emerge that have more expressive power than core cognition.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Concepts